Characterization of three Arracacia xanthorrhiza Bancroft genotypes using morphological and color parameters - Pinto-Acero, Yomaira Liney; Alvarado-Gaona, Alvaro Enrique; Burgos-Avila, Yamith Ernesto; Balaguera-Lopez, Helber Enrique; Ramirez-Gonzalez, Sandra Isabel (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
In Colombia, the arrachacha is a crop with high economic and nutritional value. Despite its agricultural importance, few studies have focused on characterizing morphological parameters between genotypes. Some arracacha genotypes have been classified based on their qualitative traits such as coloration of the root, stem and leaf. Because of the variability of this characteristic, it is necessary to use the colorimetric system for greater precision. Color characterization was performed using the CIELab colorimetric system and morphological parameters (plant height, root diameter and number of fleshy roots) on three different genotypes of A. xanthorrhiza Bancroft (Yema de huevo, Paliverde and Yucatana) in the municipalities of Boyaca and Somondoco in the Department of Boyaca, Colombia. The results showed differences in the morphological characteristics plant height, root diameter and number of fleshy roots. The Yema de huevo genotype had a greater root number and diameter and a higher height, closely followed by the Paliverde genotype. This response depended on the environmental conditions of each municipality. The root and stem coloration had differences between the three genotypes, meaning these morphological characteristics can differentiate these genotypes. The Yema de huevo and Paliverde genotypes had the highest color index, a response that depended on the characteristics of each municipality. This research provides information on the physical characteristics of each genotype, which allows for easier visual identification.